2013
DOI: 10.1055/s-0033-1354382
|View full text |Cite
|
Sign up to set email alerts
|

Force-Velocity Profile: Imbalance Determination and Effect on Lower Limb Ballistic Performance

Abstract: This study sought to lend experimental support to the theoretical influence of force-velocity (F-v) mechanical profile on jumping performance independently from the effect of maximal power output (P max ). 48 high-level athletes (soccer players, sprinters, rugby players) performed maximal squat jumps with additional loads from 0 to 100% of body mass. During each jump, mean force, velocity and power output were obtained using a simple computation method based on flight time, and then used to determine individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
198
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(248 citation statements)
references
References 29 publications
12
198
1
5
Order By: Relevance
“…Force-velocity profile and optimal profile Samozino et al [9,21] have clearly shown, using a theoretical approach [10] confirmed by experimental evidence [19,26], that SJ height was almost entirely explained by the following variables: Pmax, hPO and the slope of the Fv profile. Thus, added to the previous section about the influence of hPO, it is clear that the relationship between maximal jump height and Pmax is confounded by the balance between the athletes' force and velocity capabilities, as described by their Fv profile.…”
Section: 3mentioning
confidence: 76%
See 2 more Smart Citations
“…Force-velocity profile and optimal profile Samozino et al [9,21] have clearly shown, using a theoretical approach [10] confirmed by experimental evidence [19,26], that SJ height was almost entirely explained by the following variables: Pmax, hPO and the slope of the Fv profile. Thus, added to the previous section about the influence of hPO, it is clear that the relationship between maximal jump height and Pmax is confounded by the balance between the athletes' force and velocity capabilities, as described by their Fv profile.…”
Section: 3mentioning
confidence: 76%
“…Thus, added to the previous section about the influence of hPO, it is clear that the relationship between maximal jump height and Pmax is confounded by the balance between the athletes' force and velocity capabilities, as described by their Fv profile. The two implications shown by Samozino et al's works are that (i) for a same hPO and Pmax, different levels of SJ height may be achieved depending on the Fv profile of the athletes and (ii) the theoretical maximal SJ height for a given individual (given their hPO and Pmax) is only reached if the actual Fv profile is equal to the calculated optimal Fv profile (and in this case, body mass is the Lopt) [8,10,19,26]. In other words, an athlete with an optimal Fv profile for jump height will have his own body mass as Lopt, and thus produce Pmax during vertical jump without additional load.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, given that our findings demonstrate the significant impact of resistance ratio on force and movement velocity, the type of resistance modality can be considered as an interesting exercise variable that can be adjusted to induce the targeted gains in force or velocity. On the other hand, for athletes with similar maximal power capability, a significant imbalance between force and velocity capacities can negatively impact their respective ballistic performance 30 .…”
Section: Conclusion and Practical Applicationsmentioning
confidence: 99%
“…The parameters obtained from the linear F-V relationship have consistently revealed high reliability (Jaric, 2015). In addition, the abilities to generate high movement velocity or resistance to high external load have been shown to be determined by V 0 (Feeney, Stanhope, Kaminski, Machi, & Jaric, 2016) and F 0 (Driss, Vandewalle, Le Chevalier, & Monod, 2002), respectively, while ballistic performance is largely dependent not only on P M (Samozino, Rejc, Di Prampero, Belli, & Morin, 2012;Vandewalle, Peres, Heller, Panel, & Monod, 1987) but also on an optimum balance between F 0 and V 0 (i.e., F-V slope) (Jiménez-Reyes, Samozino, Brughelli, & Morin, 2017;Samozino et al, 2014).…”
Section: Introductionmentioning
confidence: 99%